The Ammonium/Nitrate Ratio Affects the Growth and Shikonin Accumulation in Arnebia euchroma - Linyuan Shi; Jiuwen Liang; Ruishan Wang; Xiufu Wan; Binbin Yan; Yan Zhang; Meilan Chen; Changzheng Liu; Qi Li; Sheng Wang; Lanping Guo (Agronomy, 2023)
Nitrogen (N) strongly affects plant growth and metabolism. Although ammonium toxicity has been reported, the effects of nitrogen on shikonin biosynthesis remain obscure. In this study, we tested four different concentrations of NH4+ on Arnebia euchroma hairy roots (AEHR) to clarify the influence of NH4+ on the growth of AEHR and on shikonin accumulation in them and the possible mechanisms. The results showed that compared with the 0% NH4+ treatment (only nitrate as a nitrogen source), the 10% NH4+ treatment increased the fresh weight and the dry weight of AEHR and promoted the synthesis of shikonins. In contrast, the 20% NH4+ treatment started to show inhibition effects on the growth of and shikonin accumulation in AEHR, and the 30% NH4+ treatment exhibited the strongest inhibition effects. With an increased percentage of NH4+, the AEHR became shorter and thicker, with more branches. To further elucidate the mechanisms, we analyzed the time course of nitrogen assimilation, the gene expression level of key enzymes involved in shikonin biosynthesis pathway, and the content of various endogenous hormones in the presence of toxic NH4+ concentrations. The results indicated that auxin and cytokinin might regulate the growth and architecture of AEHR under NH4+ toxicity and revealed that the jasmonate level was reduced along with the inhibition of shikonin biosynthesis. This first comprehensive investigation of the effects of the ammonium/nitrate ratio on shikonin biosynthesis not only provides valuable data for optimizing the in vitro culture of A. euchroma and its shikonin production, but also suggests potential fertilizing strategies for its cultivation.